Relationships between live animal ultrasound predicted intramuscular fat and shear force in fed cattle - Keenan, L.D.; Moser, Daniel W.; Eborn, D.R.; Marston, T.T. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Approximately 280 Simmental- and Hereford- sired feedlot steers were ultrasonically evaluated for intramuscular fat deposition using CPEC and Critical Vision, Inc. (CVI) ultrasound systems. Warner-Bratzler shear force measurements were taken on steaks from the 13th rib region. Differences between CPEC and CVI ultrasound and actual marbling measurements were corrected for bias and identified as CPEC deviation and CVI deviation. Correlation coefficients and linear models were used to determine if shear force values were associated with amount of intramuscular fat predicted by the ultrasound systems. Correlation coefficients of CPEC deviation and CVI deviation with shear force were 0.18 and 0.15, respectively. This indicates that animals overestimated for marbling by ultrasonic measures had a tendency to have higher shear force values. However, when the data were evaluated with linear models, which take many variables into account, we found that animals with ultrasound marbling predictions higher than the actual carcass marbling score were not associated with higher shear force values. Thus, animals with a higher marbling prediction are not associated with an unfavorable increase in shear force values. Selecting animals for increased marbling through ultrasound evaluation should have neither a favorable nor unfavorable effect on tenderness.
Keywords: Beef; Ultrasound; CPEC and Critical Vision, Inc. (CVI) ultrasound systems; Intramuscular fat; Shear force